Finding the Needle in the Hay Stack: Population-based Study of Prediagnostic Symptomatic Interval in Children With CNS Tumors. Issue 8 (November 2021) - Goldman, Ran D.; Cochrane, D. Douglas; Dahiya, Anita; Mah, Heidi; Buttar, Arsh; Lambert, Clare; Cheng, Sylvia
Abstract : Central nervous system (CNS) tumors in children are a devastating diagnosis and delay in diagnosis is well documented in the literature. The aim of this study was to document and characterize time to diagnosis of CNS tumors among children 0 to 17 years of age in a pediatric center. A retrospective chart review was conducted of medical records of children with CNS tumors from 2000 to 2016 in British Columbia, Canada and 148 reports were available for review. Average age at diagnosis was 87.8 months (SD=59.7; median=72). One third (30%) were diagnosed after a single visit to a health care provider and 11 (7.7%) after more than 4 visits. Median time to diagnosis (prediagnostic symptomatic interval [PSI]) was 62 days (average 197±341 d; range, 0 to 2047 d). Longest period was time from first symptom to first health care provider visit (PSI1, median 37 d). Tumors in the posterior fossa and symptoms of ataxia or paresis were associated with a significantly shorter PSI. CNS tumors in children continue to pose a diagnostic challenge with variability in time to diagnosis. Our population-based study suggests variability in time to diagnosis with a need for education of families to identify symptoms associated with CNS tumors.